Production and hematological parameters of heifers ½ Angus ½ Nellore raised in integrated livestock forestry system - da Cruz Gonçalves, Juliene [UNESP]; Andrighetto, Cristiana [UNESP]; Mateus, Gustavo Pavan; Simiele, Carolina Barone [UNESP]; Sekiya, Bianca Midori Souza [UNESP]; Oba, Eunice [UNESP]; Dias, Beatriz Poletto Neris [UNESP]; da Silva, Ben Hur Aparecido [UNESP]; Martinez, Edgar Ramos [UNESP]; Duarte, Julia Paschoareli Ferro [UNESP]; Gonela, Renan Fabrício [UNESP]; Oliveira, Juliana Moura [UNESP] (Springer Nature, 2025)
The objective of this study was to evaluate the effect of integrated livestock forestry system (ILF) in the performance, thermal comfort, hematological and hormonal parameters of ½ Angus ½ Nellore heifers, in summer. Thirty-two heifers were distributed in randomized block design with two treatments and four replications. The treatments were: CPS: Conventional pasture system without trees; ILF: integrated livestock forestry system with eucalyptus planted in triple lines (386 eucalyptus ha−1). Forage dry mass (FDM), bromatological and morphological analysis of Marandu palisadegrass, animal performance, ambient temperature (TA), relative humidity (RH), and humidity index (THI), respiratory rate (RR), blood count and hormonal parameters were evaluated. FDM, stem, senescent material and dry matter were lower in the ILF. The crude protein was high in ILF. There was no significant difference for final weight and average daily gain between treatments. The stocking rate and weight gain per area were higher in CPS. The TA, RH, THI and RR were better in the ILF. The leukocytes and albumin were higher in the ILF. There was no significant difference between the treatments for T3, T4 and cortisol. The ILF reduces FDM depending on shading and promotes relevant changes in the morphological and bromatological composition, but it is not able to change the performance of heifers. The arboreal component improves the thermal comfort indexes, which is reflected in the RR and in the greater number of leukocytes and albumin, showing that ILF is important for the heifers welfare.
Keywords: Commercial cross breeding; Thermalcomfort; Welfare